Values in urban design: A design studio teaching approach. (March 2017) - Chiaradia, Alain J.F.; Sieh, Louie; Plimmer, Frances
Abstract : Since 2000, research into the value of urban design has been utilised in consultancy and policy-making with regard to understanding the value of public investment. This research informs an emerging approach to teaching urban design appraisal within a MA urban design studio, in which variations of the residual method are deployed to assess developer value, private good and public good. Here, the relationship of the appraisal and design elements is articulated by an iterative model of design decision and design judgement making. By situating this approach in a broader theory of societal value, we reconceptualise from first principles, the concept of 'value in urban design'. This also suggests a corresponding definition of urban design in terms of value. Highlights: Teaching of property valuation within urban design studio enhances 'designer' judgement. Such judgement skills are transferable, yet enable context-specific urban design: places and people and their assemblages. 'Value in urban design' conceptualised within a social-scientific value discourse. A value based definition of urban design.